Proximate composition and seed lipid components of “kabuli”-type chickpea (Cicer arietinum L.) from Argentina - Marioli Nobile, Carla Georgina; Carreras, Julia; Grosso, Rubén; Inga, Claudia Marcela; Silva, Mercedes Pilar; Aguilar, Roxana; Allende, María José; Badini, Raul; Martinez, Maria Jose (Scientific Research Publishing, 2019)
Chickpea is an important pulse crop with a wide range of potential nutritional benefits because of its chemical composition. The purpose of the cur- rent work was to provide the chemical composi- tion of “kabuli”-type chickpea (Cicer arietinum L.) developed in Argentina for nutritional pur- pose. Protein, oil and ash contents, fatty acid, tocopherol and mineral element compositions were studied. Among the studied genotypes, protein content ranged from 18.46 to 24.46 g/100g, oil content ranged from 5.68 to 9.01 g/100g and ash from 3.55 to 4.46 g/100g. Linoleic, oleic and palmitic acids were the most abundant fatty ac- ids. The average oleic-to-linoleic ratio was 0.62 and average iodine value was 117.82. Tocopherols, well-established natural antioxidants, were found in chickpea seeds in relatively similar amounts across all genotypes. Mineral element analysis showed that chickpea was rich in macronutri- ents such as K, P, Mg and Ca. The nutritional composition of chickpea genotypes developed and grown in Argentina provides useful infor- mation for breeding programs, food marketing and consumers and establishes chickpea as component of a balanced human diet.